Evidence of seasonal price transmission in the soybean international Market (Economia Aplicada, 2004)
The paper aims consists to analyze price transmission system in soybean international market. Initially is determined the price causality in soybean international market utilizing prices series from Chicago Board ofTrade (CBOT), Rotterdam, Brazil and Argentina, production and commercialization main centers. Second, seasonal behavior of the price series was evaluated using X-12 method. The results obtained showed that causality directions among the analyzed price series are unidirectional. The seasonal behavior analysis indicated that Rotterdam price, at the crop time in South Hemisphere, is more similar to Brazilian and Argentina prices. On the other hand, Rotterdam prices align with CBOT quotation in North Hemisphere crop time. This result is due to the fact that soybean consumption in European Union, the largest international soybean buyer, to remains constant during the year. Last, the paper concludes that international soybean market presents a price transmission system based on seasonal behavior.